PENGARUH KEBIJAKAN HUTANG TERHADAP KINERJA KEUANGAN MELALUI KEBIJAKAN DIVIDEN PERUSAHAAN FOOD AND BEVERAGE Tbk di BEI TAHUN 2012-2016 - jurnalpps pps; Baiq Gati Andayani Wulandari; Novrida Qudsi Latfillah; Muninghar Muninghar (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
The purpose of this study is to prove and analyze the significant influence on the finance of food andbeverage companies; to prove and analyze the significant influence on food and beverage companydividend policies; to prove and analyze the significant effect of dividends on the financial performanceof food and beverage companies. This type of research is causal. The population and sample in this studywere Food and beverage companies that produced 14 Indonesian Stock Exchanges in the 2012-2016period. The analysis technique in this study is path analysis. The results in this study indicate thatdecisions do not significantly affect the performance of companies in food and beverage companies thathave an influence on the Indonesia Stock Exchange for the period 2012-2016; the policy does not partiallyaffect the dividend policy in food and beverage companies that have an influence on the Indonesia StockExchange for the period 2012-2016; dividend policy on company performance in food and beveragecompanies that affect the Indonesia Stock Exchange for the period 2012-2016.Keywords: debt policy, dividend policy, company performance